EFFECT OF HHVT VALUE OF RAW MATERIALS OF PINE WOOD CHARCOAL AND COFFEE WOOD CHARCOAL (70%:30%, 30%:70% & 50%:50%) WITH MESH SIZES 100 AND 250 ON THE HEALTH VALUE: PENGARUH NILAI HHVT BAHAN BAKU BRIKET ARANG KAYU PINUS DAN ARANG KAYU KOPI (70%:30%, 30%:70% dan 50%:50%) DENGAN UKURAN MESH 100 DAN 250 TERHADAP NILAI KALOR - Yosia Kurnia Putra Susanto Nuham; Nereus Tugur Redationo; Bernardus Crisanto Putra Mbulu (Mechanical, Energy and Material (METAL), 2026)
Through this study, there are two variables of concern, namely the effect of the initial comparison of the combustion of raw materials of pine wood charcoal & coffee wood charcoal (70%: 30%, 30%: 70% and 50%: 50%) with mesh sizes of 100 and 250. The initial process of the study is the manufacture of charcoal in pine wood and coffee wood briquettes, pine wood and coffee wood are processed by carbonization at a temperature of 500°C, crushed, sieved using mesh 100 and 250, variations of 70%: 30%, 30%: 70% and 50%: 50% mixed with adhesive, given a pressure of 4 kg, and dried at a temperature of 80°C for 3 hours. The purpose of this study is to determine the comparative value of the combustion rate and calorific value of each briquette sample. The methodology used in this study is to conduct experiments on pine wood charcoal briquettes and coffee wood charcoal in testing the calorific value and combustion rate. From the research that has been done, it was found that the burning rate of briquette samples with variations of pine and coffee wood charcoal with variations of 70%: 30% mesh 100, the burning time is 189 minutes, while at mesh 250 the burning time is 215 minutes. The variation of briquette samples 30%: 70% at mesh 100 the burning time is 192 minutes and mesh 250 is 194 minutes. The variation of briquette samples 50%: 50% mesh 100 has a burning time value of 19 minutes and mesh 250 is 155 minutes. For coffee wood charcoal briquettes and pine wood charcoal at mesh 250 it can be said to meet the SNI 01-6235-2000 standard because the calorific value produced is ≥5000 cal / gram.